2018
DOI: 10.1186/s13054-018-2125-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of procalcitonin-guided antibiotic treatment on clinical outcomes in intensive care unit patients with infection and sepsis patients: a patient-level meta-analysis of randomized trials

Abstract: BackgroundThe clinical utility of serum procalcitonin levels in guiding antibiotic treatment decisions in patients with sepsis remains unclear. This patient-level meta-analysis based on 11 randomized trials investigates the impact of procalcitonin-guided antibiotic therapy on mortality in intensive care unit (ICU) patients with infection, both overall and stratified according to sepsis definition, severity, and type of infection.MethodsFor this meta-analysis focusing on procalcitonin-guided antibiotic manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(159 citation statements)
references
References 45 publications
6
135
1
17
Order By: Relevance
“…Interestingly, the mortality rate in PCT-guided patients was also significantly lower compared with the control group (21.1 vs. 23.7%, p ¼ 0.03). 54 Similar effects were also noted in subgroup analyses stratified by Sepsis-3 definition, severity of sepsis, presence of renal shock, renal failure and type of infection. These positive effects may be explained by a lower risk for antibiotic side effects with PCT-guided care.…”
Section: Therapeutic Biomarkers For Antibiotic Stewardship In the Icusupporting
confidence: 54%
“…Interestingly, the mortality rate in PCT-guided patients was also significantly lower compared with the control group (21.1 vs. 23.7%, p ¼ 0.03). 54 Similar effects were also noted in subgroup analyses stratified by Sepsis-3 definition, severity of sepsis, presence of renal shock, renal failure and type of infection. These positive effects may be explained by a lower risk for antibiotic side effects with PCT-guided care.…”
Section: Therapeutic Biomarkers For Antibiotic Stewardship In the Icusupporting
confidence: 54%
“…Procalcitonin is demonstrating promise in individualizing antibiotic use. Evidence shows that this proinflammatory biomarker safely shortens antibiotic duration in critically ill patients in the ICU [36,37], and has been demonstrated to reduce mortality [38] in these and other patients. In a recent Cochrane Review, the use of procalcitonin to guide initiation and duration of antibiotic treatment resulted in lower risks of mortality, lower antibiotic consumption, and lower risk for antibiotic-related side effects [39].…”
Section: Duration Of Antibiotic Agents and Biomarkersmentioning
confidence: 99%
“…Changes in serum CRP levels during the first 48 h after antibiotic initiation can help evaluate the response to initial antimicrobial therapy [27]. Likewise, a PCT-based algorithm may help reduce antibiotic exposure in septic patients without compromising clinical outcomes [28,29]. However, not all studies have shown the same positive effect [30], suggesting that the effectiveness of PCT-based algorithms may depend on the physician's experience and the clinical setting.…”
Section: Discussionmentioning
confidence: 99%